SISTEM PAKAR DIAGNOSA PENYAKIT PADA AYAM TERNAK MENGUNAKAN METODE CERTAINTY FACTOR BERBASIS WEBSITE - Nanda Cahyo Winoto; Achmad Hlindasyah (Journal of Research and Publication Innovation, 2023)
In this research, the author conducted a study to apply the Certainty Factor method in diagnosing diseases in poultry and building an application using information technology. The use of expert systems and artificial intelligence has become a solution for identifying diseases in poultry infected with viruses or bacteria. The Certainty Factor method is used to accommodate the uncertainty of a specialist's thinking and describe the level of confidence that the specialist has towards the problem of diseases suffered by poultry infected with dangerous viruses. The results of this study indicate that the author has successfully built an expert system for diagnosing diseases in poultry using the Certainty Factor method, including conducting system requirement analysis, calculating using the Certainty Factor method, designing the system using UML, designing the database, designing the user interface, and developing a web-based system.